A tool for measuring ecological literacy: coupled human-ecosystem interactions. Issue 1 (1st January 2021) - Casper, Anne Marie A.; Fernández-Giménez, María E.; Balgopal, Meena M.
ABSTRACT: Purpose: Ecological and natural resource management (NRM) decisions have far-reaching implications for global ecological change. Because beliefs influence behaviors, it is vital that decision-makers' beliefs reflect the shift to include humans as an integrated component of ecosystems. Our study, grounded in socio-cultural theory, analyzed how undergraduate participants situated humans in relation to ecosystems and describes the continuum we developed to characterize individuals' conceptions. Design/Methodology/Approach: To develop a grounded theory we analyzed participants' perceptions of human-environment relationships through semi-structured interviews. We used both triangulation of codes through student course artifacts and inter-rater coding to establish trustworthiness of findings. Findings: We present a continuum of coupled human-ecosystems conceptions developed from the participants' conceptions: (i) exclusion, (ii) uncertain-exclusion, (iii) uncertain, (iv) uncertain-inclusion, and (v) inclusion. Practical Implications: Our tool is useful for NRM educators and professionals to assess how people perceive human-environment relationships and to study shifts in ecological literacy. Theoretical Implications: If people believe that humans are independent from ecosystems, their decisions about interacting with the environment will reflect this. Each individual contributes to societal practices through the officials, policies, and causes they support, and their consumption and land management decisions. Without a conception of ecosystems that includes humans, future NRM professionals may select policies and practices that result in ineffective or destructive management. Originality/Value: Our study responds to the need for an instrument that measures how people situate humans in relationship to ecosystems that is open-ended, can be used across a variety contexts, and does not require specialized statistical knowledge. GRAPHICAL ABSTRACT: